The role of the Erasmus + welcome project "Towards Incoming International University Communities" in the development of the process of internationalization of the KSMU - Myrzahmetova, Kamila (KAZGUU University, Nazarbayev University, 2018)
The internationalization of modern higher education is conditioned by objective processes of globalization in all spheres of human life.
Keywords: internationalization; marketing; "Ambassador"; international interuniversity networks; international projects